BROODSTOCKS SELECTION PRACTICES AMONG HATCHERIES IN PENINSULAR MALAYSIA - Jumain, Nora Azura; Ali, Fazlin; Sharifuddin, Juwaidah; Mohd Nawi, Nolila; Chong, Chou Min (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The fisheries sector plays a vital role in ensuring protein security in Malaysia. However, heavy dependence on marine capture fisheries has contributed to declining fish stocks, raising concerns over long-term sustainability. Aquaculture has therefore been identified as a key strategy to enhance fish production and meet national food security goals under the National Agro-Food Policy 2 (NAP 2). Despite this, aquaculture production in Malaysia remains below targeted levels, largely due to limitations in the quantity and quality of fish fry supplied to grow-out farms. As fish fry quality is closely linked to broodstock management, effective broodstock selection practices are critical for sustainable aquaculture development. This study examined current broodstock selection practices among hatchery operators in Peninsular Malaysia, as hatcheries serve as the primary source of fish fry for the aquaculture sector. Data were collected from hatchery operators and analysed using descriptive statistics and chi-square analysis. The results indicate that farmers mainly rely on manual selection criteria, particularly broodstock size, physical appearance, and weight. Chi-square analysis further revealed that farm size, labour availability, and production system significantly influence the extent to which farmers evaluate broodstock physical traits, health status, growth rate, and weight. Larger farms and farms with more workers demonstrated a greater capacity to apply multiple broodstock assessment criteria. These findings highlight that broodstock selection practices are shaped not only by farmers’ experience and knowledge but also by structural farm capacity. The study provides empirical evidence to support targeted policy interventions, including scale-appropriate broodstock management guidelines and labour-efficient assessment tools. Improving broodstock selection practices at the hatchery level has the potential to enhance fish fry quality, increase aquaculture productivity, and support Malaysia’s efforts to meet national fish production targets sustainably.